The impact of CYP2C9, VKORC1, and CYP4F2 polymorphisms on warfarin dose requirement in Saudi patients - Jokhab, Salha; AlRasheed, Maha M.; Bakheet, Dana; AlMomen, Abdulkareem; AlAboud, Nouf; Kamali, Farhad (Frontiers in Pharmacology, 2025)
BackgroundLimited data are available on factors that affect warfarin dose requirement in Saudi patients. Saudis are among the underrepresented ethnic groups in warfarin pharmacogenetics research. The present study investigated the frequency of CYP2C9*2 and*3, CYP4F2 (G1347A) and VKORC1 –1639G>A genotypes and their impact on warfarin dose requirement in a cohort of Saudi patients requiring anticoagulation therapy.Methods193 patients on chronic warfarin therapy and with stable anticoagulation took part in the study. Genotyping for VKORC1 1639G>A, CYP4F2 G1347A, CYP2C9*2 430C>T and CYP2C9*3 1075A>C were performed using TaqMan genotyping assays. Analysis of variance was carried out to determine the association between CYP2C9, CYP4F2, and VKORC1 genotype and warfarin dose requirement in two groups based on target INR range. Backward linear regression analysis identified genetic and clinical factors influencing doe requirements.ResultsPatients with CYP2C9 and VKORC1 polymorphisms required significantly lower warfarin doses compared to wild-type patients. Carriers of two mutant alleles required lower doses than those with one mutant allele. In contrast, CYP4F2 polymorphisms did not influence warfarin dose. Age and genetic variants in CYP2C9 and VKORC1 were negatively correlated with dose requirements, while body surface area (BSA) was positively correlated.ConclusionSaudi patients with polymorphisms in CYP2C9 and VKORC1 required lower warfarin doses than those with the wild-type allele. CYP4F2 polymorphism had no effect on warfarin dose requirement. Integrating patient clinical factors, including age and BSA, and genetic polymorphisms in CYP2C9 and VKORC1 provides the best estimation of factors contributing to warfarin dose in the Saudi patient population.